Artificial Intelligence and Machine Learning in Clinical Medicine, 2023 - Haug, Charlotte J.; Drazen, Jeffrey M. (The New England journal of medicine, 2023)
This first article in a series describes the history of artificial intelligence in medicine; the use of AI in image analysis, identification of disease outbreaks, and diagnosis; and the use of chatbots.